PENGARUH MATA KULIAH KOMUNIKASI POLITIK ISLAM TERHADAP MINAT LITERASI POLITIK MAHASISWA FAKULTAS DAKWAH DAN KOMUNIKASI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research aims to analyze the influence of the Islamic Political Communication course on students' interest in political literacy at the Faculty of Da'wah and Communication, UIN Alauddin Makassar. The background to this research is based on the importance of political literacy in forming critical political understanding and participation among students. Along with the development of information technology, political literacy becomes increasingly important to support students' active involvement in political issues. The research method used is quantitative with a survey approach. The population of this study were students from the Faculty of Da'wah and Communication who had taken the Islamic Political Communication course. The research sample was chosen randomly and consisted of 100 respondents. Data is collected through questionnaires that measure political knowledge, political participation, and understanding of political issues. Data analysis was carried out using a simple linear regression technique to determine the influence of the Islamic Political Communication course on students' interest in political literacy. The research results show that the Islamic Political Communication course has a significant influence on increasing students' interest in political literacy. The correlation coefficient between course variables and interest in political literacy shows a strong positive relationship. This means that the higher the students' understanding of the Islamic Political Communication course, the higher their interest in political literacy. The conclusion of this research is that the Islamic Political Communication course plays an important role in increasing students' interest in political literacy. This research implies the need to improve the quality of teaching in Islamic Political Communication courses to support better political literacy among students. The recommendation of this research is for lecturers to be more innovative in teaching methods and utilize technology to enrich lecture material, as well as encourage students to be more actively involved in discussions and political activities.